Teaching mathematics using snakes and ladders game to help students understand angle measurement. (February 2020) - Vitoria, L; Ariska, R; Farha,; Fauzi,
Abstract: Mathematics for young learners should be taught in a fun way, using a familiar context. Incorporating games into the classroom is a way to engage students in mathematics and hence improve their learning outcomes. This article reports a qualitative study conducted to improve students' understanding of angle measurement by implementing snakes and ladders game. A class consisted of 30 fourth-grade students at a primary school in Banda Aceh, Indonesia, participated in the study. Data on the students' activity during learning and their learning outcomes were collected using observation sheet and tests. Results showed that the implementation of the snakes and ladders game in the teaching and learning of angles successfully improved the students' attention during learning and their interactions with the teacher and their peers. There was also a significant improvement in the students' learning outcomes from the average score of 45 for pre-test to 85 for post-test. These findings suggest that the implementation of snakes and ladders game is beneficial for students' mathematics learning.